KONVERSI MINYAK BIJI KAPUK MENJADI BIODIESEL MENGGUNAKAN KATALIS CaO/HTC - Yustia Wulandari Mirzayanti; Kartika Udyani; Rizky Cahyaningsih; M. Puguh Tri Darmawan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
This research focuses on producing biodiesel through the transesterification process of Ceiba pentandra triglyceride acid using a CaO/Hydrotalcite (CaO/HTC) catalyst. This study aimed to determine the effect of adding catalyst mass, the mole ratio of oil: methanol to biodiesel yield, and knowing the FAME content of biodiesel yield and the highest impact of adding catalyst mass and the ratio kapok seed oil to FFA conversion results. Kapok seed oil was transesterified for 2 hours at a temperature of 65°C. The molar ratio of oil and methanol used is 1:5, 1:10, 1:15, 1:20, and 1:25 (%wt). The catalyst used is CaO/HTC, with 3.0977 grams of CaO and 30.9023 grams of hydrotalcite. The best results for biodiesel yield at the ratio of the oil: methanol molar ratio of 1:15 with a catalyst mass of 1.5% wt, which is 66%, while the best % conversion of FFA is in the ratio of oil: methanol molar ratio of 1:25 with a catalyst mass of 1.5%wt which is 90.674%. FAME content of the yield The highest biodiesel contains C15-C26 carbon chains and is dominated by Linoleic Acid Methyl Ester compounds.